Epidemiological impacts on hospitalizations for pathologies of the blood and hematopoietic organs in the 4th health regional in the State of Paraná between 2017 and 2021 (Research, Society and Development, 2023)
Objective: To describe and compare hospitalization data for diseases of the blood and hematopoietic organs and some immune disorders in the 4th health regional in the State of Paraná between the years 2017 to 2021. Methodology: This is a retrospective epidemiological descriptive study, based on in secondary data, from the Hospital Information System (SIH), in the Department of Informatics of the Unified Health System (DATASUS). Results: 708 hospital admissions were cataloged by ICD-10 - Chapter III: Diseases of the blood and hematopoietic organs and some immune disorders (D50-D89), considering public and private hospitals, and all categories of care. The predominant color/race mentioned was ''white'' nº 613, 86.6%. The genders evidenced in the hospitalizations in these periods, presented similarities between the sexes. As for the age group, between 60 and 69 years old, they had a higher number of hospitalizations, followed by the age group between 70 and 79 years old. It was also presented the variables referring to the average length of hospitalization, the values of hospital services, average values of hospitalizations per morbidity list. In the period surveyed, 44 deaths were recorded. Conclusion: It was shown the need for greater care on the part of health professionals in the subject and epidemiology of hospitalizations for diseases of the blood and hematopoietic organs and some immune disorders. It is noticed, the current lack of health services regarding the prevention of an avoidable pathology. The guarantee of qualified access to primary health care for the most vulnerable populations is evident. It is imperative that healthcare professionals are aware of these conditions.